Environment-friendly high-content calcium carbonate bio-based thermoplastic elastomer composition, preparation method and application thereof
Patent Information
- Application Number
- CN202610198750.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-11
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-02-11
AI Technical Summary
然而,无机填料表面亲水,与疏水性高分子基体相容性差,简单共混时易团聚,尤其在填料含量较高时会导致分散不均,造成拉伸强度与伸长率下降、冲击脆性增加以及表面“白化”等问题
[0092] 1. This invention provides an environmentally friendly thermoplastic elastomer composition that uses bio-based environmentally friendly resin and natural rubber as the polymer matrix, and fills it with a high content of inexpensive inorganic filler calcium carbonate, while possessing mechanical properties and injection molding processability equal to or better than existing petroleum-based TPE or TPR materials. This invention optimizes the type, content, and combination of the components constituting the composition, particularly by introducing a special additive system that maximizes the interfacial compatibility between the bio-resin, natural rubber, and inorganic filler, enabling the high content of inorganic filler to form a uniformly dispersed and stable phase structure within the polymer matrix.
Smart Images

Figure CN121873516B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, specifically to an environmentally friendly high-content calcium carbonate bio-based thermoplastic elastomer composition and its preparation method and application. Background Technology
[0002] Thermoplastic elastomers (TPEs / TPRs) are polymeric materials that exhibit rubber-like elasticity at room temperature and can be melt-processed at high temperatures. They are widely used in automotive parts, electronic products, daily necessities, and medical products, often serving as a substitute for rubber. Common commercial thermoplastic elastomers include styrene-based (TPS), olefin-based (TPO), and polyurethane-based (TPU).
[0003] However, most TPE / TPR currently rely on petroleum-based monomers for synthesis, which not only involves large amounts of carbon dioxide emissions, exacerbating global warming, but is also affected by oil price fluctuations, resulting in unstable costs, and will also cause environmental pollution after disposal.
[0004] In recent years, with increasingly stringent global environmental regulations and the rise of sustainable development concepts, the research and development of bioplastics has received growing attention. Bioplastics generally refer to polymeric materials based on biomass raw materials or biodegradable materials, but most of them have high hardness and low elongation, making them difficult to directly replace TPE / TPR, which require flexibility and elasticity. Although there have been studies on improving brittleness by blending flexible polymers or plasticizers, bio-based TPE / TPR materials with performance comparable to commercial TPE / TPR have not yet been developed.
[0005] On the other hand, to reduce costs, adjust performance, and improve environmental friendliness, inorganic fillers such as calcium carbonate, talc, and clay are often added to polymers. Calcium carbonate, due to its wide availability, low price, and safety, has become one of the most commonly used fillers. However, inorganic fillers have hydrophilic surfaces and poor compatibility with hydrophobic polymer matrices. They are prone to agglomeration during simple blending, especially at higher filler contents, leading to uneven dispersion, decreased tensile strength and elongation, increased impact brittleness, and surface "whitening."
[0006] Existing technologies still struggle to achieve both good mechanical properties and processability when combining high-content inorganic fillers with bio-based resins. If the system simultaneously contains three components with significantly different properties—bioresin, natural rubber, and high-content inorganic fillers—achieving a uniform microstructure and good compatibility becomes particularly difficult.
[0007] Therefore, there is an urgent need to develop a new type of thermoplastic elastomer composition and its preparation technology, whose main component is bio-based resin and can be incorporated with a high content of inexpensive inorganic fillers, so as to achieve excellent mechanical and processing properties while maintaining environmental advantages and cost competitiveness, in order to replace traditional petroleum-based TPE / TPR. Summary of the Invention
[0008] To address the aforementioned challenges of directly replacing TPE / TPR, which require flexibility and elasticity, with bioplastics, and the difficulty in achieving both good mechanical properties and processability when combining high-content inorganic fillers with bio-based resins, and the difficulty in achieving a uniform microstructure and good compatibility when the system simultaneously contains three components with significantly different properties—bio-resin, natural rubber, and high-content inorganic fillers—this invention aims to solve these problems. Its main objective is to provide an environmentally friendly thermoplastic elastomer composition that uses bio-based environmentally friendly resin and natural rubber as the polymer matrix, filled with a high content of inexpensive inorganic filler calcium carbonate, and possesses mechanical properties such as tensile strength, elongation, elastic recovery, and flexibility equal to or better than existing petroleum-based TPE or TPR materials, as well as injection molding processability. The specific technical solution is as follows:
[0009] An environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, comprising, by weight, 10-45 parts of bio-based thermoplastic resin, 5-15 parts of natural rubber, 30-55 parts of modified calcium carbonate, 3-10 parts of vegetable oil-based plasticizer, 0.5-5 parts of interface compatibilizer, and 0-5 parts of additives. The bio-based thermoplastic resin forms the continuous phase matrix, and the natural rubber forms the dispersed phase within the bio-based thermoplastic resin matrix.
[0010] This invention uses a bio-based thermoplastic resin as the continuous phase and introduces natural rubber as the dispersed phase. During shear processing, a uniform microstructure is formed, which allows the dispersed rubber phase to absorb energy and provide resilience when the material is deformed by external force. The bio-based resin continuous phase ensures the thermoplastic processing capability of the material. Compared with the brittle fracture of pure bio-based resin, the composition exhibits a better elastic recovery rate under large deformation.
[0011] Specifically, the natural rubber of this invention is a natural polymer collected from the sap of rubber trees, giving the composition of this invention excellent elasticity, elongation, and resilience. The natural rubber of this invention is dispersed in a fine-grained form within a bio-based thermoplastic resin matrix to form a dispersed phase, absorbing external stress energy and recovering from deformation. If the content of natural rubber is too low, sufficient elasticity will be difficult to achieve; if the content of natural rubber is too high, the viscosity will increase excessively, processability will deteriorate, and mechanical strength will decrease. In this invention, to maximize the dispersibility of the natural rubber, it is preferable to use natural rubber in dry powder form.
[0012] Calcium carbonate is the most abundant inorganic filler in this invention, playing a role in reducing the cost of the composition, improving dimensional stability, and enhancing rigidity. On the one hand, if the amount of calcium carbonate in traditional bio-based materials is less than 30 parts, the cost-saving effect is negligible and the rigidity enhancement effect is insufficient; if the amount exceeds 55 parts, it is difficult to disperse no matter how the surface treatment is performed, resulting in a sharp deterioration in processability, a serious decrease in mechanical properties, and often problems such as decreased tensile strength and brittleness. On the other hand, if the calcium carbonate particle size is too small, the agglomeration phenomenon will be aggravated, leading to difficulties in dispersion; if the particle size is too large, it will damage the surface appearance of the molded product and lead to a decrease in physical properties. This invention uses modified calcium carbonate to improve the wettability between inorganic fillers and hydrophobic polymer matrices. The modified calcium carbonate surface changes from hydrophilic to oleophilic, reducing the surface energy barrier of the filler and avoiding particle agglomeration at high content. Combined with the bridging effect of the interface compatibilizer, it enhances the interfacial adhesion between the inorganic and organic phases, enabling the filler to play the roles of filling cost reduction, rigid support, and stress transfer in the system. Thus, while maintaining a high filler content, the tensile strength and elongation reach a level comparable to petroleum-based TPE / TPR.
[0013] Furthermore, vegetable oil-based plasticizers act as compatibility enhancers, improving the compatibility between bio-based thermoplastic resins and natural rubber. These plasticizers penetrate the molecular chains of both bio-based thermoplastic resins and natural rubber, increasing free volume and weakening intermolecular forces. By lowering the glass transition temperature and melt viscosity of the system, they improve the material's flexibility and elongation during processing. Simultaneously, they give highly filled systems good melt flowability, meeting the requirements of conventional injection molding processes and solving common problems such as surface roughness and difficult demolding in highly filled systems. However, if the amount of vegetable oil-based plasticizer is less than 3 parts, its plasticizing effect is insufficient, leading to decreased flexibility; if the amount exceeds 10 parts, the strength of the composition decreases, and plasticizer exudation to the surface of the molded product may occur.
[0014] To address the significant differences in properties between bio-based resins, natural rubber, and inorganic fillers, the interfacial compatibilizer of this invention is located at the interface between bio-based resins, natural rubber, and surface-treated calcium carbonate, which have different polarities. Through the polar groups and non-polar segments on the compatibilizer's molecular chain, it can reduce the interfacial tension between the components and induce chemical or physical bonding. This plays a decisive role in preventing phase separation and enhancing interfacial adhesion, preventing whitening caused by peeling at the interface under external stress, thereby improving the tensile strength, elongation, impact resistance, and other mechanical properties of the composition. If the amount used is less than 0.5 parts, its compatibilizing effect is negligible; if the amount used exceeds 5 parts, unreacted compatibilizer will act as an impurity, leading to a decrease in physical properties or unnecessary increase in manufacturing costs.
[0015] This invention, by using 30-55 parts of calcium carbonate, can reduce the formulation cost of bio-based TPE / TPR, offsetting the high raw material cost of bio-based resins; at the same time, the main components of the composition are all biologically derived or natural inorganic minerals, which can increase the biomass content of the material, reduce the carbon footprint of the product, and meet the demand for environmentally friendly materials in the fields of coating materials, daily necessities, and automotive interior materials.
[0016] Furthermore, the bio-based thermoplastic resin includes one or more combinations of polybutylene succinate, polycaprolactone, polylactic acid, polybutylene terephthalate-adipate, and polyhydroxyalkanoates.
[0017] The bio-based thermoplastic resin of the present invention is biodegradable, enabling the final product to enter a controlled biological cycle after disposal, which helps to reduce the environmental burden.
[0018] Specifically, polylactic acid (PLA) provides high tensile strength and rigidity, while polybutylene terephthalate (PET) and polycaprolactone (PVC) exhibit good flexibility and elongation at break. Furthermore, PET and PVC contain numerous ester bonds, exhibiting good reactivity with the interfacial compatibilizers in this system. This facilitates the reduction of surface tension in the natural rubber phase during melt blending, promotes the fine dispersion of rubber particles in the resin matrix, resulting in improved material toughness, and suppresses interfacial tearing that may occur in high-filler systems under tension.
[0019] Among them, resins such as polycaprolactone and polybutylene succinate have low glass transition temperatures. Combined with the vegetable oil-based plasticizer in the system, the composition of the present invention can still maintain good molecular chain segment mobility in low-temperature environments, avoiding the defect of traditional bioplastics being prone to brittleness at low temperatures, and enabling the elastomer to maintain stable physical and mechanical properties in outdoor or low-temperature storage and transportation environments.
[0020] In addition, bio-based thermoplastic resins such as polybutylene succinate and polyhydroxyalkanoates have specific melt rheological properties. In a high-filler system containing 30-55 parts of modified calcium carbonate, they can form a continuous phase with moderate viscosity, effectively coating inorganic particles and ensuring that the composition has sufficient melt strength and fluidity during injection molding. This reduces the risk of melt fracture caused by excessive filler content and ensures the surface finish and dimensional stability of the molded parts.
[0021] Optionally, in some embodiments, using a mixture of polybutylene succinate, polycaprolactone, and polylactic acid (PLA) resins allows for the utilization of the strengths of each resin while mitigating their weaknesses. Polybutylene succinate possesses excellent biodegradability and flexibility, exhibits good compatibility with other bio-resins, and is suitable for forming the basic framework of the composition. Polycaprolactone has a low glass transition temperature, providing excellent flexibility even at low temperatures, and plays a role in controlling the crystallization of other resins and improving overall elasticity. PLA is a rigid resin with high tensile strength and elastic modulus, enhancing the overall mechanical strength of the composition. Insufficient content of these bio-resins may decrease the strength and processability of the composition, while excessive content may lead to insufficient flexibility and elasticity.
[0022] Furthermore, vegetable oil-based plasticizers include one or more combinations of epoxidized soybean oil, epoxidized linseed oil, and citrate plasticizers.
[0023] This invention selects epoxidized soybean oil, epoxidized linseed oil, or citrate esters as vegetable oil-based plasticizers. Because the system contains 30-55 parts of high-calcium carbonate, the melt exhibits high internal friction and viscosity during processing. The vegetable oil-based plasticizer, with its long aliphatic molecular chains, can penetrate between the molecular chains of bio-based resins and at the filler interface, acting as a lubricant, reducing the melt viscosity and extruder current of the composition, improving the melt's mold-filling ability during injection molding, and ensuring the molding quality of complex structural parts.
[0024] Specifically, the epoxy groups and ester groups contained in the molecular structures of epoxidized soybean oil and epoxidized linseed oil, and the multiple ester groups or hydroxyl groups contained in citrate plasticizers, interact with the polar groups of bio-based polyester resin through polar functional groups. At the same time, they also have a compatibilizing effect with the non-polar natural rubber phase, which helps to reduce the interfacial tension between the continuous phase of bio-based resin and the dispersed phase of natural rubber, promotes the stability of the two-phase structure, and has an auxiliary effect on improving the interfacial wettability of inorganic fillers and polymer matrix.
[0025] Furthermore, citrate plasticizers such as acetyl tributyl citrate have good compatibility with bio-based resins such as polylactic acid or polybutylene succinate. By weakening the secondary bond interactions between polymer chains, they lower the glass transition temperature of the matrix resin. When subjected to external impact or stretching, the plasticized matrix can alleviate stress concentration through chain segment movement, and work synergistically with the natural rubber phase to improve the elongation at break and low-temperature resistance to brittleness of the composition.
[0026] In addition, the epoxy groups contained in the molecules of epoxidized soybean oil and epoxidized flaxseed oil have an acid absorption effect. During high-temperature processing, they can neutralize the trace organic acid and other degradation products that may be generated by bio-based resins, inhibit the degradation of polymer chains, act as stabilizers, ensure that the materials maintain stable mechanical properties after multiple processing cycles, and reduce the risk of yellowing of products during long-term use.
[0027] As mentioned earlier, vegetable oil-based plasticizers, as small molecule components, can pre-wet the surface of modified calcium carbonate in the early stages of mixing. This pre-wetting reduces the cohesive force between calcium carbonate particles, promoting a more uniform distribution of filler at the interface between bio-based resin and natural rubber, thus avoiding localized stress defects caused by high filler content. Compared to traditional phthalate-based petroleum-based plasticizers, the vegetable oil-based plasticizer selected in this invention has low migration and good biocompatibility. Derived from natural oils, it is non-toxic and meets environmental standards. Its polar characteristics are closer to those of bio-based resins, reducing surface blooming or odor problems caused by plasticizer precipitation during use. It is suitable for daily necessities or contact products with high safety requirements.
[0028] Optionally, in some embodiments, the vegetable oil-based plasticizer is epoxidized soybean oil with an epoxy equivalent of 6.0% or more. Epoxidized soybean oil is inexpensive, has excellent plasticizing efficiency, and provides stability against heat and light; its dosage can be increased during compounding.
[0029] Furthermore, the interface compatibilizer includes one or more combinations of maleic anhydride-grafted polyolefins, copolymers containing glycidyl methacrylate, isocyanate compounds, and organosilane compounds.
[0030] This invention selects maleic anhydride-grafted polyolefins, glycidyl methacrylate, isocyanate compounds, or organosilane compounds as interface compatibilizers. The anhydrides on the maleic anhydride-grafted polyolefin molecular chains, the epoxy groups in glycidyl methacrylate, or the isocyanates in isocyanate compounds can undergo in-situ chemical reactions with the hydroxyl or carboxyl groups at the ends of the bio-based resin. Simultaneously, their non-polar segments physically entangle with the natural rubber phase, transforming the physical interface into a covalent bond through chemical coupling, thereby improving the interfacial shear strength of the composition under stress. Organosilane compounds or graft polymers containing polar groups can pre-coat the modified calcium carbonate surface, anchoring one end to the inorganic particle surface through chemical bonds or strong physical adsorption, while the other end is compatible with the polymer matrix. This inhibits secondary aggregation between high-content calcium carbonate particles, improves the wettability of the filler in the matrix, solves the stress concentration problem caused by high filler content, and prevents whitening due to interfacial detachment during stretching.
[0031] Specifically, as an interfacial active substance, the interfacial compatibilizer can reduce the interfacial tension between the bio-based resin matrix and the natural rubber dispersion phase. During the melt mixing process, it is beneficial for the rubber phase to undergo more delicate cracking under shear force, forming submicron-sized uniformly dispersed particles. By refining the microstructure, it can prevent crack propagation and synergistically improve the elongation at break and impact strength of the material.
[0032] In addition, interface compatibilizers enhance the thermodynamic stability of the system during high-temperature processing by coating and anchoring the interfaces of each phase. They prevent abnormal polymerization or phase separation of the dispersed phase in the high shear and high temperature environment of injection molding, ensure the stability of melt flow, reduce defects such as flow marks and delamination on the surface of the product, and enable the mass production of complex irregular parts to have better dimensional consistency.
[0033] Based on the above setup, through the compatibilizer enhancement and filler dispersion improvement, this invention combines polar bio-based resin, non-polar natural rubber, and inorganic filler with a highly polar surface. Through multi-dimensional interface repair, the components are transformed from mechanical blending into an organically synergistic whole. While maintaining a high filler ratio, it achieves comprehensive physical properties close to those of petroleum-based TPE / TPR.
[0034] As mentioned above, interfacial compatibilizers can chemically react with the hydroxyl and carboxyl groups of bioresins, the double bonds of natural rubber, or the functional groups on the surface of calcium carbonate to form a strong interfacial bond. Maleic anhydride-grafted polyolefins can be selected from maleic anhydride-grafted polypropylene and maleic anhydride-grafted polyethylene. In some embodiments, the maleic anhydride-grafted polypropylene used as a compatibilizer has polypropylene chains that are physically compatible with the non-polar natural rubber domains, and the grafted maleic anhydride groups can form chemical bonds such as ester bonds with the polar bioresin and calcium carbonate surface.
[0035] Furthermore, the modified calcium carbonate is surface-modified by a surface treatment agent, which includes one or more combinations of stearic acid, titanate coupling agent, aluminate coupling agent, stearate, oleate, and palmitate.
[0036] This invention uses stearic acid, long-chain fatty acid salts, titanate esters, or aluminate ester coupling agents to modify the surface of calcium carbonate. Natural calcium carbonate contains a large number of polar groups such as hydroxyl groups on its surface, exhibiting strong hydrophilicity and poor interfacial compatibility with non-polar natural rubber and weakly polar bio-based resins. By coating the surface with stearic acid or long-chain fatty acid salts, the hydrophobic groups are oriented on the filler surface, reducing the surface energy of calcium carbonate and allowing the filler to be better wetted by the polymer matrix during blending, achieving an effective combination of inorganic and organic phases.
[0037] In the case of 30-55 parts of calcium carbonate in this invention, the untreated filler is prone to secondary agglomeration due to van der Waals forces, forming microscopic defects. The titanate or aluminate coupling agent forms a monolayer coating on the surface of calcium carbonate and generates a steric hindrance effect between particles, which destroys the cohesive effect between particles, so that the filler is uniformly distributed as fine particles in the matrix, avoiding stress concentration and ensuring the mechanical continuity of the material during the tensile process.
[0038] Among them, titanate and aluminate coupling agents have a bifunctional structure. One end reacts chemically with the hydroxyl groups on the surface of calcium carbonate to form a covalent bond, while the other end physically entangles or chemically couples with the molecular chains of bio-based resins or natural rubber. Through molecular bridging, they enhance the shear strength of the phase interface, enabling the material to transfer stress from the matrix to the rigid filler when subjected to external forces. This suppresses interfacial detachment and whitening during the stretching process while maintaining a high filling amount.
[0039] As mentioned above, the modified calcium carbonate has a lower surface friction coefficient, which acts as an internal lubricant to reduce friction between the filler and the polymer molecular chain, reduce the viscosity and heat accumulation of the system during melt mixing, prevent bio-based resin from degrading due to overheating, and improve the flowability during extrusion and injection molding. The composition of the modified calcium carbonate used in this invention has a better melt flow rate at the same processing temperature, and the surface of the product is relatively smooth and fine.
[0040] Specifically, the organic coating layer formed on the surface of calcium carbonate by the surface treatment agent can reduce the adsorption of moisture in the air by inorganic particles and inhibit the hydrolytic degradation of moisture-sensitive bioplastics such as polybutylene succinate and polylactic acid during storage and use. At the same time, the tight interfacial bonding between the modified filler and the matrix reduces the generation of micropores and improves the density consistency and mechanical property stability of elastomer products during long-term use.
[0041] Furthermore, the additives include one or more of antioxidants, ultraviolet stabilizers, heat stabilizers, lubricants, pigments, flame retardants, and antibacterial agents. The amount of antioxidant used is 0.1 to 3 parts. The antioxidants include hindered phenolic primary antioxidants and phosphite secondary antioxidants mixed in a weight ratio of 1:1 to 1:3.
[0042] Furthermore, as a preferred embodiment of the invention and not a limitation thereof, the invention employs a mixture of hindered phenolic primary antioxidant and phosphite secondary antioxidant in a weight ratio of 1:1 to 1:3. During the melt processing stage, the phosphite secondary antioxidant decomposes the hydroperoxides generated by bio-based resins and natural rubber, inhibiting chain initiation reactions. During the product use stage, the hindered phenolic primary antioxidant provides long-term thermal stability by capturing free radicals. Through the synergistic effect of primary and secondary antioxidants, it prevents the thermal degradation of bio-based resins under high shear and high-filling environments, thus keeping the rate of decline in the physical and mechanical properties of the material after multiple thermal cycling processes within a low range.
[0043] Because this invention contains a high content of bio-based components and natural rubber, it is prone to oxidation and discoloration at high processing temperatures. By introducing antioxidants, the oxidation induction period of the material is extended, color fluctuations during molding are suppressed, and the original whiteness of the product is guaranteed. Combined with UV stabilizers, the material's resistance to photo-oxidative aging in outdoor exposure environments can be improved, preventing surface cracking or powdering. The antioxidant dosage is 0.1 to 3 parts, ensuring that the small molecule additives do not cause severe blooming or precipitation on the material surface.
[0044] In some embodiments, the lubricant migrates to the surface during the melt cooling process, forming an extremely thin lubricating layer, which reduces the adhesion between the product and the mold cavity, shortens the injection molding cycle, and eliminates surface flow marks or roughness caused by high calcium carbonate content, resulting in a smoother feel and appearance for the product.
[0045] In addition, in some embodiments, the application range of the material can be expanded by introducing functional additives such as flame retardants, antibacterial agents or pigments; the addition of antibacterial agents, in conjunction with natural rubber components, enhances the material's resistance to mildew in humid environments, while the addition of flame retardants improves the safety of the material in the fields of electronic appliances and automotive interior parts.
[0046] Optionally, in some embodiments, the ultraviolet stabilizer includes at least one of HALS light stabilizer and benzotriazole UV absorber.
[0047] Optionally, in some embodiments, the heat stabilizer includes one or more of triphenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, and pentaerythritol diphosphite (2,4-di-tert-butylphenyl) bis(2,4-di-tert-butylphenyl) phosphite.
[0048] Optionally, in some embodiments, the lubricant includes one or more of butyl stearate, pentaerythritol tetrastearate, ethylene bis-stearamide, polyethylene wax, and oxidized polyethylene wax.
[0049] Furthermore, the modified calcium carbonate has an average particle size of 0.5 to 5 µm, the amount of surface treatment agent is 0.5 to 3.0% of the total weight of calcium carbonate, and the modified calcium carbonate is distributed in a monodisperse form in the continuous phase and the dispersed phase.
[0050] Furthermore, as a preferred embodiment of the invention and not a limitation thereof, particles in the range of 0.1 to 10 µm can be used without impairing the physical properties of the final product. In this invention, fine calcium carbonate particles with an average particle size of 0.5 to 5 µm are preferably used.
[0051] This invention controls the calcium carbonate particle size within the range of 0.5 to 5 µm, achieving good dimensional compatibility with the bio-based resin matrix and the natural rubber dispersed phase. Within this particle size range, calcium carbonate particles can induce moderate crazing and shear banding in the matrix under stress, absorbing impact energy. If the particle size is too small, irreversible agglomeration is likely to occur at high filler concentrations of 30-55 parts; if the particle size is too large, it is prone to becoming stress concentration points, leading to early fracture. This particle size range balances the specific surface area and dispersion difficulty of the filler, ensuring that it is uniformly distributed in a monodisperse form in the continuous and dispersed phases after interfacial modification, maintaining the toughness of the elastomer while ensuring the rigidity of the material.
[0052] This invention controls the amount of surface treatment agent to 0.5 to 3.0% of the weight of calcium carbonate, which can ensure that a complete molecular coating layer is formed on the surface of each inorganic particle. This can effectively shield the active hydroxyl groups on the surface of calcium carbonate, inhibit the aggregation of particles caused by hydrogen bonding, and avoid the precipitation of small molecules or the formation of a weak lubrication layer at the interface due to excessive modifier. This allows the filler to form a stable physical anchoring or chemical bond with the polymer matrix.
[0053] Specifically, modified calcium carbonate is distributed monodispersely in both the continuous and dispersed phases, with filler particles existing independently as individuals. This allows external loads to be uniformly transferred to each hard phase particle through the polymer matrix, avoiding stress voids caused by localized filler accumulation and improving the brittle fracture problem of highly filled elastomers at the microscopic level. Since modified calcium carbonate is not only present in the resin matrix but also distributed within the dispersed phase of natural rubber, its global distribution enhances the cohesive strength of the phase interfaces. This helps stabilize the dispersed structure of natural rubber during processing, preventing abnormal aggregation or merging of the rubber phases under high temperature and high shear, ensuring the consistency of the material's mechanical properties in different directions, and improving the dimensional accuracy and deformation stability of injection molded parts.
[0054] As mentioned above, the appropriate particle size and good monodispersity enable the polymer molecular chains to tightly wrap the filler particles and move together when the material undergoes large-scale tensile deformation, rather than creating tiny air gaps at the particle edges. Through interfacial wettability and deformation synchronization, the change in refractive index caused by the detachment of calcium carbonate from the matrix is suppressed, thus improving the tensile whitening problem common in highly filled bio-based materials and maintaining the color stability of the product appearance.
[0055] Specifically, monoalkoxy titanate and aluminate coupling agents are readily hydrolyzed in water, losing their coupling activity. Wet modification causes them to decompose significantly before contacting the filler, resulting in extremely low efficiency. Dry modification, on the other hand, avoids hydrolysis and allows them to react effectively on the filler surface through heat and shear force. Furthermore, stearic acid and sodium stearate are water-insoluble solids and can be easily mixed at high speed using a dry method, utilizing mechanical force and frictional heat to adhere to and to some extent embed them into the filler surface. However, sodium oleate and sodium palmitate are water-soluble soaps. If used alone in the high-temperature, high-speed mixing environment of a dry process, they are prone to absorbing moisture, clumping, and sticking to the walls, resulting in extremely uneven dispersion and poor modification effect. If sodium oleate or sodium palmitate powder is premixed and finely ground with a large amount of calcium stearate or a small amount of stearic acid powder and other dry hydrophobic carriers in a ball mill or high-speed mixer, the hydrophobic carrier powder can coat or adsorb onto the surface of the water-soluble soap salt particles, forming a "core-shell" structure or a uniform composite powder. This can reduce the hygroscopicity and stickiness of the soap salt particles, allowing them to form a hydrophobic powder in the subsequent mixing with hot calcium carbonate, thereby improving dispersibility.
[0056] Specifically, the modified calcium carbonate of this invention undergoes surface treatment using a mature and low-cost dry modification process. When the surface treatment agent is stearic acid, the specific modification steps for the modified calcium carbonate are as follows:
[0057] M1. Drying and preheating: Add heavy calcium carbonate with an average particle size of 2µm into a high-speed mixer and stir and dry at 100-110℃ to remove surface moisture;
[0058] M2. Add modifier: Add stearic acid at a weight of 1.0-2.0% of calcium carbonate. Use the high-speed shear heat of the mixer and external heating to melt the stearic acid, which has a melting point of 69.6℃.
[0059] M3. Surface coating reaction: Raise the temperature to 110-130℃ and stir at high speed at 1500-2000rpm for 10-15 minutes; at this time, stearic acid reacts chemically with the hydroxyl groups on the surface of calcium carbonate to form a calcium stearate layer, and at the same time, the coating is completed through physical adsorption.
[0060] M4. Cooling and Discharging: Reduce the rotation speed and cool to below 60°C before discharging to obtain active calcium carbonate powder with a hydrophobic surface.
[0061] Furthermore, another object of the present invention is to provide a method for preparing an environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, involving an optimized manufacturing process for preparing the composition, comprising the environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition as described above, including the following steps:
[0062] S1, dried bio-based thermoplastic resin and modified calcium carbonate; the moisture content after drying is controlled below 0.05%;
[0063] S2. In a twin-screw extruder, dried bio-based thermoplastic resin is melt-blended at a temperature of 120 to 230°C to form a continuous phase; the twin-screw extruder used is a co-rotating twin-screw extruder with an aspect ratio of 30 to 50; during blending, the screw rotation speed is maintained in the range of 150 to 250 rpm.
[0064] S3. Add natural rubber, vegetable oil-based plasticizer, interface compatibilizer, and additives to the continuous phase and apply shear force to mix them.
[0065] S4. Dry modified calcium carbonate is added to the mixture from step S3 via a side feeder for fine dispersion; Temperature setting: gradually increase from the feed port to the die head and then slightly decrease (130℃→160℃→150℃) to prevent thermal degradation of natural rubber.
[0066] S5. After the final mixture is extruded through a die and cooled, it is cut into granular shapes to obtain the finished product. The specific gravity of the composition is 1.2 to 1.5, and the resilience is more than 50%.
[0067] The specimens prepared from the composition have a Shore A hardness of 60 to 95 according to ASTM D2240, a tensile strength of ≥8 MPa according to ASTM D412, and an elongation at break of ≥300%.
[0068] This invention first dries the bio-based thermoplastic resin in steps S1 to S2 and then melts it at 120 to 230°C. This ensures that the matrix resin, as the continuous phase, is fully melted in a low-moisture environment. Gradient heating is used to prevent hydrolytic degradation of the bio-based resin at high temperatures and in the presence of moisture, thus ensuring the molecular weight stability of the continuous phase and providing sufficient melt strength for subsequent accommodating high-content fillers. Specifically, to prevent a decrease in physical properties caused by moisture, the resin is thoroughly dried at 80 to 100°C for at least 2 hours to minimize moisture content.
[0069] Alternatively, using a twin-screw extruder or kneader, the dried bio-based thermoplastic resin is melt-blended in a temperature range of 120 to 180°C to form a continuous phase. However, this temperature can be adjusted within a range above the melting point and below the thermal decomposition temperature of the bio-resin used, and depending on the type of resin used, it can be extended to, for example, a range of 120 to 230°C. If the temperature is too low, the resin cannot melt completely, resulting in uneven mixing; if the temperature is too high, the resin will undergo thermal decomposition. In this case, the screw speed is adjusted to a range of 100 to 300 rpm to ensure the resin melts fully and mixes evenly. Furthermore, during blending, the screw rotation speed is maintained within a range of 180 to 220 rpm; the main screw speed is kept constant, set at 200 rpm to provide a stable shear rate.
[0070] In step S3, natural rubber, plasticizer, and compatibilizer are pre-added to the molten continuous phase and shear force is applied. This causes the plasticizer to preferentially wet the resin molecular chains, reducing the system viscosity. Simultaneously, the high shear field of the twin-screw extruder shears the natural rubber into micron-sized dispersed particles, while the compatibilizer migrates to the interface between the rubber and resin for coating. In this step, the chemical reaction induced by the interfacial compatibilizer is active, forming a strong interfacial bond between the components.
[0071] Step S4 involves feeding modified calcium carbonate using a side feeder. This avoids premature contact between the filler and the low-temperature solid polymer, preventing feeding difficulties. Compared to one-time feeding through the main feed port, side feeding avoids interference from powder in the resin melting process, reducing screw venting pressure and wear. Simultaneously, the filler is dispersed within the formed resin-rubber mixture, utilizing the viscous shear force of the melt to break up the calcium carbonate particles, achieving a monodisperse distribution in both the continuous and dispersed phases. During calcium carbonate feeding, the screw speed and feeding rate are appropriately adjusted to induce uniform dispersion within the matrix, preventing agglomeration. Step S5 involves extruding the fully mixed and dispersed final molten mixture through a die, cooling, and granulating it. This granule shape facilitates transportation and storage, and allows for direct use in subsequent injection molding and other processing, simplifying the product manufacturing process and improving production efficiency and batch stability.
[0072] This invention controls the mixing temperature between 120 and 230°C, which covers the processing window of bio-based resins while taking into account the heat resistance of natural rubber. By controlling the residence time and thermal history of the material in the extruder, it ensures the full mixing of each component and the chemical coupling reaction of the compatibilizer, while preventing the premature volatilization of vegetable oil-based plasticizers or the thermal failure of additives, thus ensuring the stability of the physical properties of the finished granules.
[0073] Specifically, in step S5, the molten mixture is extruded through an extruder die in the form of strands. After being cooled and solidified by a cooling water tank, it is cut into granules of a certain size using a pelletizer. Through extrusion, cooling, and granulation in step S5, this invention transforms complex chemical formulas into standardized industrial granules. This continuous production process ensures that the ratio of bio-based resin, natural rubber, and calcium carbonate in each granule is consistent, improving the yield of subsequent injection molding. At the same time, this method is compatible with existing twin-screw extrusion equipment, without the need for additional complex equipment, and has good prospects for industrial application.
[0074] The manufacturing method of the present invention optimizes the order of input and mixing conditions by taking into account the characteristics of each component, and is designed to form a uniform and stable microstructure even in complex multi-component systems containing high content of inorganic fillers.
[0075] Furthermore, the bio-based thermoplastic resin is fed into the main feed port of the twin-screw extruder, the natural rubber, interface compatibilizer, and some additives are fed into the first side feed port of the twin-screw extruder, the vegetable oil-based plasticizer is fed into the liquid injection port of the twin-screw extruder, and the modified calcium carbonate is fed into the second side feed port of the twin-screw extruder. The first side feed port is close to the main feed port, and the liquid injection port is located between the first side feed port and the second side feed port.
[0076] This invention allows bio-based thermoplastic resin and some additives, such as lubricants, to be fed into the self-feeding port, ensuring that the matrix material undergoes a complete melting, plasticizing, and conveying process throughout the screw. This facilitates the matrix material's role as a continuous phase to coat other components and avoids the problem of uneven multiphase mixing caused by incomplete resin melting.
[0077] Specifically, natural rubber, an interface compatibilizer, and some additives are fed into the first side feed port, which is close to the main feed port. Utilizing the high-viscosity shear field of the matrix resin upon melting, the natural rubber is rapidly sheared and broken down. Because the compatibilizer is added simultaneously, its active groups immediately accumulate at the interface between the rubber droplets and the resin melt, stabilizing the dispersed structure through in-situ coupling reactions and preventing secondary agglomeration of the rubber particles. Of course, in some embodiments, all additives can also be fed into the first side feed port.
[0078] In this process, a vegetable oil-based plasticizer is introduced between the first and second side feed ports through a liquid injection port, which can plasticize the initially mixed resin-rubber mixture. Injecting liquid at this time can effectively reduce the melt viscosity of the system, prepare the rheology for the subsequent introduction of high-content fillers, and avoid slippage of the main feed section caused by premature addition of plasticizer, thus ensuring the screw conveying efficiency. At the same time, it allows the plasticizer to penetrate evenly into the polymer chains, rather than being adsorbed by the filler in advance.
[0079] In addition, adding modified calcium carbonate at the second downstream feed port can shorten the residence time of inorganic hard particles in the screw and reduce the abrasive wear of the screw and barrel caused by 30-55 parts of high-content filler. Since the matrix has been fully plasticized and the viscosity has been reduced at this time, calcium carbonate can be quickly wetted by the melt and achieve monodisperse distribution, effectively reducing local overheating caused by high-intensity friction between the filler and the screw, and protecting the heat-sensitive bio-based resin from degradation.
[0080] This invention optimizes the melting, shearing, wetting, and venting functions of each section of the twin-screw extruder by first constructing a continuous phase, then stabilizing the dispersed phase, and finally introducing the filler phase. This results in a finished product with a more uniform microstructure, while avoiding ineffective friction and repeated shearing of materials within the barrel, reducing energy consumption per unit output, and improving overall production efficiency.
[0081] Typically, as the content of inorganic fillers increases, the flexibility and tensile properties of materials decrease sharply, and their processability also deteriorates. The composition of this invention minimizes the use of petroleum-based resins, primarily using bioplastics and natural rubber derived from renewable plant resources, as well as calcium carbonate, an abundant natural mineral, as the main raw materials.
[0082] Therefore, compared with existing petroleum-based TPE or TPR materials, the product's overall carbon footprint can be reduced by more than 40%, effectively meeting global environmental regulations and contributing to sustainable industrial development. Furthermore, the bio-resins and natural rubber used are biodegradable under certain conditions, thus mitigating the environmental pollution burden upon disposal.
[0083] This invention significantly reduces raw material costs by reducing the amount of expensive polymer resins used and by using up to 30 to 55 parts of relatively inexpensive inorganic filler calcium carbonate, which helps to improve the price competitiveness of the final product and expand its market influence.
[0084] This invention optimizes the types and contents of each component, particularly through the combined application of specially surface-treated calcium carbonate, highly efficient interfacial compatibilizers, and vegetable oil-based plasticizers. Even in a highly filled state, the interfacial bonding force between the bio-resin, natural rubber, and calcium carbonate is maximized, exhibiting excellent tensile strength, elongation, elastic recovery, and flexibility comparable to existing commercial petroleum-based TPE / TPR. Furthermore, the masterbatch prepared by this invention exhibits good flowability during injection molding, fewer molding defects, and is easily processed into products of various shapes.
[0085] Furthermore, another object of the present invention is to provide an application of an environmentally friendly, high-calcium carbonate bio-based thermoplastic elastomer composition. Moreover, the present invention relates to a sustainable and environmentally friendly material that can replace petroleum-based materials, while simultaneously satisfying excellent mechanical properties and processability requirements. The present invention also relates to various molded articles prepared using the composition, comprising the environmentally friendly, high-calcium carbonate bio-based thermoplastic elastomer composition as described above, which is prepared into finished products through one or more of injection molding, extrusion molding, blow molding, and 3D printing processes. These finished products include soft product materials for various industrial fields requiring flexibility and elasticity, such as mobile device housings, wire and cable sheathing materials, tools, handles, shoe soles, toys, and automotive interior parts.
[0086] The composition of this invention, due to the use of vegetable oil-based plasticizers and gradient processing technology, exhibits stable rheological behavior of the melt over a wide temperature range. In injection molding, it demonstrates good mold filling flow and demolding performance, making it suitable for complex mobile device housings; in extrusion molding, the melt strength is sufficient to support stable wire and cable sheathing and continuous production of profiles; simultaneously, its thermoplastic properties are also compatible with 3D printing and blow molding processes, providing process freedom for the development of products with different shapes.
[0087] For applications involving human contact such as handles, tools, and toys, the composition of this invention uses an interface compatibilizer to microscopically lock 30-55 parts of high-content calcium carbonate, overcoming the surface roughness and whitening defects common in traditional high-filling materials. The finished product has a delicate surface, no exudates, and has a skin-like feel and anti-slip properties comparable to petroleum-based TPE / TPR, improving the sensory quality and safety of the product.
[0088] In applications such as shoe soles and automotive interior parts, the natural rubber dispersed phase in the composition provides the necessary dynamic elasticity and fatigue resistance, while the high content of modified calcium carbonate acts as a rigid support phase, improving the wear resistance and deformation stability of the product. Through the combination of soft and hard properties, the finished product can maintain long-term dimensional stability when subjected to frequent compression or impact, and is not prone to permanent deformation.
[0089] As a coating material for wires and cables, the calcium carbonate particles in the composition of this invention are distributed in a monodisperse state, which effectively blocks the migration path of moisture and ions and improves the volume resistivity of the material. At the same time, in combination with the composite antioxidant system, the coating material can still maintain a good physical barrier function under long-term electric heating or environmental exposure conditions, preventing the coating layer from becoming brittle or cracking prematurely.
[0090] Since the composition of this invention is mainly composed of bio-based resin, natural rubber and inorganic mineral powder, it can reduce the dependence of the finished product on petroleum-based raw materials and does not contain phthalate plasticizers, thereby enhancing the environmental competitiveness of the end product in the international market, while reducing the long-term environmental burden caused by waste products.
[0091] The present invention has the following beneficial effects:
[0092] 1. This invention provides an environmentally friendly thermoplastic elastomer composition that uses bio-based environmentally friendly resin and natural rubber as the polymer matrix, and fills it with a high content of inexpensive inorganic filler calcium carbonate, while possessing mechanical properties and injection molding processability equal to or better than existing petroleum-based TPE or TPR materials. This invention optimizes the type, content, and combination of the components constituting the composition, particularly by introducing a special additive system that maximizes the interfacial compatibility between the bio-resin, natural rubber, and inorganic filler, enabling the high content of inorganic filler to form a uniformly dispersed and stable phase structure within the polymer matrix.
[0093] 2. The preparation method of the present invention is controllable, so as to prepare an environmentally friendly high-content calcium carbonate bio-based thermoplastic elastomer composition with high yield and excellent mechanical strength. The optimal manufacturing process conditions established by the present invention for preparing the composition can minimize the thermal decomposition of each component while inducing effective mixing and dispersion, and finally produce granules, thereby providing a manufacturing method that can be easily applied to various molding processes.
[0094] 3. The present invention provides a molded article prepared using an environmentally friendly thermoplastic elastomer composition. The molded article simultaneously meets the requirements of excellent physical properties and environmental protection, and can be used as soft parts in various industrial fields such as mobile device shells, wire sheaths, handles, automotive interior materials, etc. Attached Figure Description
[0095] Figure 1 This is a schematic diagram of the microstructure of the composition of the present invention. Detailed Implementation
[0096] To enable those skilled in the art to better understand the technical solutions described in this invention, the following embodiments are provided for illustration. Unless otherwise specified, the raw materials, reagents, or devices used in the following embodiments can be obtained from conventional commercial channels or by existing known methods.
[0097] An environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, comprising, by weight, 10-45 parts of bio-based thermoplastic resin, 5-15 parts of natural rubber, 30-55 parts of modified calcium carbonate, 3-10 parts of vegetable oil-based plasticizer, 0.5-5 parts of interface compatibilizer, and 0-5 parts of additives. The bio-based thermoplastic resin forms the continuous phase matrix, and the natural rubber forms the dispersed phase within the bio-based thermoplastic resin matrix.
[0098] The bio-based thermoplastic resin includes one or more combinations of polybutylene succinate, polycaprolactone, polylactic acid, polybutylene terephthalate-adipate, and polyhydroxyalkanoates.
[0099] Polybutylene succinate: BioPBS FZ71PM (PTT MCC Biochem Co., Ltd.), melt index (MFI) 22g / 10min (190℃, 2.16kg).
[0100] Polycaprolactone: Capa 6500 (Perstorp), molecular weight (Mw) approximately 50,000 g / mol, melting point (Tm) 60℃.
[0101] Polylactic acid: Ingeo 4032D (NatureWorks LLC), MFI 7g / 10min (210℃, 2.16kg), melting point (Tm) 160-170℃.
[0102] Polybutylene terephthalate (PET): whshuer (Wuhan Shuer), melting point (Tm) 110-120℃, melt index (MFI) ≤5g / 10min (190℃, 2.16kg).
[0103] Polyhydroxyalkanoate: F1006 (Mirel, USA), molecular weight: 500,000-800,000, glass temperature: -20℃ to 0℃, melting point (Tm) 160-170℃
[0104] Natural rubber is processed from standard Malaysian rubber (SMR) L grade into dry powder for use.
[0105] Vegetable oil-based plasticizers include one or more combinations of epoxidized soybean oil, epoxidized linseed oil, and citrate plasticizers.
[0106] The epoxidized soybean oil used is from the Sichaohai brand, with an epoxy equivalent of over 6.5%.
[0107] The epoxidized flaxseed oil uses ADK CIZER O-180A, which has an ethylene oxide oxygen content of over 8.0%.
[0108] The citrate plasticizer used is acetyl tributyl citrate from Qilu Lanfan.
[0109] Interface compatibilizers include one or more combinations of maleic anhydride-grafted polyolefins, copolymers containing glycidyl methacrylate, isocyanate compounds, and organosilane compounds.
[0110] Maleic anhydride-grafted polyolefins can be selected from maleic anhydride-grafted polypropylene. The grafting rate of maleic anhydride-grafted polypropylene is 1.2wt%, and the MFI is 110g / 10min (230℃, 2.16kg).
[0111] The copolymer containing glycidyl methacrylate is made of polypropylene grafted with glycidyl methacrylate.
[0112] The isocyanate compound used is diphenylmethane diisocyanate.
[0113] The organosilane compound used is vinyltriethoxysilane.
[0114] Furthermore, the modified calcium carbonate is surface-modified by a surface treatment agent, which includes one or more combinations of stearic acid, titanate coupling agent, aluminate coupling agent, stearate, oleate, and palmitate.
[0115] The stearic acid is from Omya, Omyacarb 2T-KA.
[0116] The titanate coupling agent used isopropyltriisostearoyl titanate.
[0117] The aluminate coupling agent used is distearyloxyisopropoxyaluminate.
[0118] Stearates are made from calcium stearate, oleates from sodium oleate, and palmitates from sodium palmitate.
[0119] The modified calcium carbonate of this invention undergoes surface treatment, the specific steps of which are as follows:
[0120] M1. Drying and preheating: Add heavy calcium carbonate with an average particle size of 2µm into a high-speed mixer and stir and dry at 100-110℃ to remove surface moisture;
[0121] M2, Add modifier: Add a surface treatment agent accounting for 1.0-2.0% of the weight of calcium carbonate;
[0122] M3, Surface coating reaction: Raise the temperature to 110-130℃ and stir at high speed of 1500-2000rpm for 10-15 minutes.
[0123] M4. Cooling and Discharging: Reduce the rotation speed and cool to below 60°C before discharging to obtain active calcium carbonate powder with a hydrophobic surface.
[0124] Furthermore, the additives include one or more of antioxidants, ultraviolet stabilizers, heat stabilizers, lubricants, pigments, flame retardants, and antibacterial agents. The amount of antioxidant used is 0.1 to 3 parts. The antioxidants include hindered phenolic primary antioxidants and phosphite secondary antioxidants mixed in a weight ratio of 1:1 to 1:3.
[0125] The hindered phenolic primary antioxidants are Irganox 1010 and BASF, and the phosphite secondary antioxidants are Irgafos 168 and BASF, mixed in a 1:2 ratio.
[0126] UV stabilizers include at least one of HALS light stabilizers and benzotriazole UV absorbers.
[0127] Heat stabilizers include one of the following: triphenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, and pentaerythritol diphosphite (2,4-di-tert-butylphenyl) bis(2,4-di-tert-butylphenyl) phosphite.
[0128] Lubricants include one or more of the following: butyl stearate, pentaerythritol tetrastearate, ethylene bis-stearamide, polyethylene wax, and oxidized polyethylene wax.
[0129] The flame retardant used is Clariant AP462 halogen-free flame retardant, and the antibacterial agent used is Amer ADM-Ag20PE.
[0130] The modified calcium carbonate has an average particle size of 0.5 to 5 µm, and the amount of surface treatment agent is 0.5 to 3.0% of the total weight of calcium carbonate. The modified calcium carbonate is distributed in a monodisperse form in the continuous phase and the dispersed phase.
[0131] A method for preparing an environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, involving an optimized manufacturing process for preparing the composition, comprising the environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition as described above, including the following steps:
[0132] S1, dry bio-based thermoplastic resin and modified calcium carbonate; dry thoroughly at 80℃ for more than 4 hours, and control the moisture content after drying to below 0.05%;
[0133] S2. In a twin-screw extruder, dried bio-based thermoplastic resin is melt-blended at a temperature of 120 to 230°C to form a continuous phase; the twin-screw extruder used is a co-rotating twin-screw extruder with a length-to-diameter ratio of 40 and a barrel diameter of 26 mm; the temperature distribution of the extruder from hopper to die is set to 130°C / 140°C / 150°C / 160°C / 160°C / 155°C / 150°C, and the screw rotation speed is maintained at 200 rpm.
[0134] S3. Add natural rubber, vegetable oil-based plasticizer, interface compatibilizer, and additives to the continuous phase and apply shear force to mix them.
[0135] S4. Dry modified calcium carbonate is fed into the mixture from step S3 via a side feeder for fine dispersion.
[0136] S5. After the final mixture is extruded through a die and cooled, it is cut into granular shapes to obtain the finished product. The specific gravity of the composition is 1.2 to 1.5, and the resilience is more than 50%.
[0137] The specimens prepared from the composition have a Shore A hardness of 60 to 95 according to ASTM D2240, a tensile strength of ≥8 MPa according to ASTM D412, and an elongation at break of ≥300%.
[0138] Twin-screw extruders include:
[0139] Main feed port (L / D 0): Continuous feeding of bio-based thermoplastic resin. The resin is first melt-plasticized here;
[0140] First side feed port (L / D 12-15): Add natural rubber powder, interface compatibilizer, and antioxidant. At this point, the resin has melted, which facilitates rubber dispersion and the initiation of the compatibilizer grafting reaction;
[0141] Liquid injection port (L / D 20-24): Continuously inject vegetable oil-based plasticizer through a high-pressure nozzle. Added after rubber dispersion to adjust viscosity and aid compatibility.
[0142] Second side feed port (L / D 28-32): Add surface-treated calcium carbonate. Adding it after the matrix viscosity has decreased and the compatibilizer has been activated minimizes wear on the equipment and prevents filler agglomeration.
[0143] The bio-based thermoplastic resin is fed into the main feed port of the twin-screw extruder. The natural rubber, interface compatibilizer, and some additives are fed into the first side feed port of the twin-screw extruder. The vegetable oil-based plasticizer is fed into the liquid injection port of the twin-screw extruder. The modified calcium carbonate is fed into the second side feed port of the twin-screw extruder. The first side feed port is close to the main feed port, and the liquid injection port is located between the first side feed port and the second side feed port.
[0144] Example 1
[0145] Based on the above implementation methods, Example 1 has the following implementation methods:
[0146] An environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, by weight, comprises 36 parts bio-based thermoplastic resin, 8 parts natural rubber, 45 parts modified calcium carbonate, 6 parts vegetable oil-based plasticizer, 3 parts interface compatibilizer, and 2 parts additives. The bio-based thermoplastic resin forms the continuous phase matrix, and the natural rubber forms the dispersed phase within the bio-based thermoplastic resin matrix.
[0147] The bio-based thermoplastic resin comprises 18 parts polybutylene succinate, 10 parts polycaprolactone, and 8 parts polylactic acid.
[0148] Vegetable oil-based plasticizers include epoxidized soybean oil. Maleic anhydride-grafted polyolefins are selected from maleic anhydride-grafted polypropylene.
[0149] Furthermore, the modified calcium carbonate is subjected to dry modification with stearic acid, with stearic acid accounting for 1% of the total mass of the calcium carbonate. The additives include an antioxidant, used in an amount of 2 parts, comprising a hindered phenolic primary antioxidant and a phosphite secondary antioxidant mixed in a 1:2 weight ratio. The average particle size of the modified calcium carbonate is 2 µm.
[0150] A method for preparing an environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, involving an optimized manufacturing process for preparing the composition, comprising the environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition as described above, including the following steps:
[0151] S1, dried bio-based thermoplastic resin and modified calcium carbonate;
[0152] S2. In a twin-screw extruder, dried bio-based thermoplastic resin is melt-blended at a temperature of 130 to 160°C to form a continuous phase; the twin-screw extruder used is a co-rotating twin-screw extruder with an aspect ratio of 40; during compounding, the screw rotation speed is maintained in the range of 180 to 220 rpm; the main screw speed is kept constant and set at 200 rpm to provide a stable shear rate;
[0153] S3. Add natural rubber, vegetable oil-based plasticizer, interface compatibilizer, and additives to the continuous phase and apply shear force to mix them.
[0154] S4. Dry modified calcium carbonate is fed into the mixture from step S3 via a side feeder for fine dispersion.
[0155] S5. After the final mixture is extruded through the die and cooled, it is cut into granular shapes to obtain the finished product.
[0156] The bio-based thermoplastic resin is fed into the main feed port of the twin-screw extruder, the natural rubber, interface compatibilizer, and additives are fed into the first side feed port of the twin-screw extruder, the vegetable oil-based plasticizer is fed into the liquid injection port of the twin-screw extruder, and the modified calcium carbonate is fed into the second side feed port of the twin-screw extruder. The first side feed port is close to the main feed port, and the liquid injection port is located between the first side feed port and the second side feed port.
[0157] Example 2
[0158] Based on the above implementation methods, Embodiment 2 has the following implementation methods:
[0159] An environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, by weight, comprises 42 parts bio-based thermoplastic resin, 6 parts natural rubber, 30 parts modified calcium carbonate, 5 parts vegetable oil-based plasticizer, 3 parts interface compatibilizer, and 4 parts additives. The bio-based thermoplastic resin forms the continuous phase matrix, and the natural rubber forms the dispersed phase within the bio-based thermoplastic resin matrix.
[0160] The bio-based thermoplastic resin comprises 20 parts polybutylene succinate, 12 parts polycaprolactone, and 10 parts polylactic acid.
[0161] Vegetable oil-based plasticizers include epoxidized soybean oil. Maleic anhydride-grafted polyolefins are selected from maleic anhydride-grafted polypropylene.
[0162] Furthermore, the modified calcium carbonate is subjected to dry modification with stearic acid, with stearic acid accounting for 1% of the total mass of the calcium carbonate. The additives include an antioxidant, used in an amount of 2 parts, comprising a hindered phenolic primary antioxidant and a phosphite secondary antioxidant mixed in a 1:2 weight ratio. The average particle size of the modified calcium carbonate is 2 µm.
[0163] A method for preparing an environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, involving an optimized manufacturing process for preparing the composition, comprising the environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition as described above, including the following steps:
[0164] S1, dried bio-based thermoplastic resin and modified calcium carbonate;
[0165] S2. In a twin-screw extruder, dried bio-based thermoplastic resin is melt-blended at a temperature of 130 to 160°C to form a continuous phase; the twin-screw extruder used is a co-rotating twin-screw extruder with an aspect ratio of 40; during compounding, the screw rotation speed is maintained in the range of 180 to 220 rpm; the main screw speed is kept constant and set at 200 rpm to provide a stable shear rate;
[0166] S3. Add natural rubber, vegetable oil-based plasticizer, interface compatibilizer, and additives to the continuous phase and apply shear force to mix them.
[0167] S4. Dry modified calcium carbonate is fed into the mixture from step S3 via a side feeder for fine dispersion.
[0168] S5. After the final mixture is extruded through the die and cooled, it is cut into granular shapes to obtain the finished product.
[0169] The bio-based thermoplastic resin is fed into the main feed port of the twin-screw extruder, the natural rubber, interface compatibilizer, and additives are fed into the first side feed port of the twin-screw extruder, the vegetable oil-based plasticizer is fed into the liquid injection port of the twin-screw extruder, and the modified calcium carbonate is fed into the second side feed port of the twin-screw extruder. The first side feed port is close to the main feed port, and the liquid injection port is located between the first side feed port and the second side feed port.
[0170] Example 3
[0171] Based on the above implementation methods, Embodiment 3 has the following implementation methods:
[0172] An environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, by weight, comprises 25 parts bio-based thermoplastic resin, 15 parts natural rubber, 50 parts modified calcium carbonate, 10 parts vegetable oil-based plasticizer, 2 parts interface compatibilizer, and 2 parts additives. The bio-based thermoplastic resin forms the continuous phase matrix, and the natural rubber forms the dispersed phase within the bio-based thermoplastic resin matrix.
[0173] The bio-based thermoplastic resin comprises 15 parts polybutylene succinate, 5 parts polycaprolactone, and 5 parts polylactic acid.
[0174] The vegetable oil-based plasticizer includes 7 parts epoxidized soybean oil and 3 parts epoxidized linseed oil.
[0175] The interface compatibilizer comprises 1 part maleic anhydride-grafted polypropylene and 1 part a copolymer containing glycidyl methacrylate.
[0176] Furthermore, the modified calcium carbonate is surface modified by a surface treatment agent, which includes a titanate coupling agent, accounting for 1.5% of the total mass of the calcium carbonate.
[0177] Furthermore, the additives include antioxidants, ultraviolet stabilizers, heat stabilizers, and lubricants. The amount of antioxidant is 0.1 parts, and the antioxidant includes hindered phenolic primary antioxidants and phosphite auxiliary antioxidants mixed in a 1:2 weight ratio.
[0178] The UV stabilizer includes 0.25 parts HALS light stabilizer and 0.25 parts benzotriazole UV absorber.
[0179] The heat stabilizer includes 0.9 parts of triphenyl phosphite.
[0180] The lubricant consists of 0.25 parts ethylene bis-stearamide and 0.25 parts polyethylene wax.
[0181] A method for preparing an environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, involving an optimized manufacturing process for preparing the composition, comprising the environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition as described above, including the following steps:
[0182] S1, dried bio-based thermoplastic resin and modified calcium carbonate;
[0183] S2. In a twin-screw extruder, the dried bio-based thermoplastic resin is melt-blended at a temperature of 130 to 160°C to form a continuous phase;
[0184] S3. Add natural rubber, vegetable oil-based plasticizer, interface compatibilizer, and additives to the continuous phase and apply shear force to mix them.
[0185] S4. Dry modified calcium carbonate is fed into the mixture from step S3 via a side feeder for fine dispersion.
[0186] S5. After the final mixture is extruded through the die and cooled, it is cut into granular shapes to obtain the finished product.
[0187] The bio-based thermoplastic resin and some lubricant are fed into the main feed port of the twin-screw extruder. The natural rubber, interface compatibilizer, and some additives are fed into the first side feed port of the twin-screw extruder. The vegetable oil-based plasticizer is fed into the liquid injection port of the twin-screw extruder. The modified calcium carbonate is fed into the second side feed port of the twin-screw extruder. The first side feed port is close to the main feed port, and the liquid injection port is located between the first side feed port and the second side feed port.
[0188] Example 4
[0189] Based on the above implementation methods, Embodiment 4 has the following implementation methods:
[0190] An environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, by weight, comprises 30 parts of bio-based thermoplastic resin, 5 parts of natural rubber, 55 parts of modified calcium carbonate, 10 parts of vegetable oil-based plasticizer, and 0.5 parts of interface compatibilizer. The bio-based thermoplastic resin forms the continuous phase matrix, and the natural rubber forms the dispersed phase within the bio-based thermoplastic resin matrix.
[0191] The bio-based thermoplastic resin comprises 10 parts polybutylene succinate, 10 parts polylactic acid, 5 parts polybutylene terephthalate-adipate and 5 parts polyhydroxy fatty acid ester.
[0192] Vegetable oil-based plasticizers include citrate plasticizers. Citrate plasticizers include acetylated tributyl citrate.
[0193] Interface compatibilizers include isocyanate compounds.
[0194] Furthermore, the modified calcium carbonate is surface-modified by a surface treatment agent, which includes calcium stearate, accounting for 1.5% of the total mass of calcium carbonate.
[0195] A method for preparing an environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, involving an optimized manufacturing process for preparing the composition, comprising the environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition as described above, including the following steps:
[0196] S1, dried bio-based thermoplastic resin and modified calcium carbonate;
[0197] S2. In a twin-screw extruder, the dried bio-based thermoplastic resin is melt-blended at a temperature of 130 to 160°C to form a continuous phase;
[0198] S3. Add natural rubber, vegetable oil-based plasticizer, and interfacial compatibilizer to the continuous phase and mix by applying shear force;
[0199] S4. Dry modified calcium carbonate is fed into the mixture from step S3 via a side feeder for fine dispersion.
[0200] S5. After the final mixture is extruded through the die and cooled, it is cut into granular shapes to obtain the finished product.
[0201] The bio-based thermoplastic resin is fed into the main feed port of the twin-screw extruder, the natural rubber and interface compatibilizer are fed into the first side feed port of the twin-screw extruder, the vegetable oil-based plasticizer is fed into the liquid injection port of the twin-screw extruder, and the modified calcium carbonate is fed into the second side feed port of the twin-screw extruder. The first side feed port is close to the main feed port, and the liquid injection port is located between the first side feed port and the second side feed port.
[0202] Example 5
[0203] Based on the above implementation methods, Example 5 has the following implementation method:
[0204] An environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, by weight, comprises 45 parts bio-based thermoplastic resin, 15 parts natural rubber, 30 parts modified calcium carbonate, 3 parts vegetable oil-based plasticizer, 5 parts interface compatibilizer, and 5 parts additives. The bio-based thermoplastic resin forms the continuous phase matrix, and the natural rubber forms the dispersed phase within the bio-based thermoplastic resin matrix.
[0205] The bio-based thermoplastic resin comprises 15 parts polybutylene succinate, 10 parts polycaprolactone, 10 parts polylactic acid, 5 parts polybutylene terephthalate-adipate and 5 parts polyhydroxy fatty acid ester.
[0206] Vegetable oil-based plasticizers include epoxidized soybean oil and citrate plasticizers.
[0207] Citrate plasticizers include acetyl tributyl citrate.
[0208] Interface compatibilizers include maleic anhydride-grafted polyolefins and organosilane compounds.
[0209] Maleic anhydride-grafted polyolefins are selected from maleic anhydride-grafted polypropylene.
[0210] Furthermore, the modified calcium carbonate is surface-modified by a surface treatment agent, which accounts for 2% of the total mass of the calcium carbonate. The surface treatment agent includes stearic acid and sodium oleate in a weight ratio of 1:1.
[0211] Furthermore, the additives include one or more of antioxidants, ultraviolet stabilizers, heat stabilizers, lubricants, pigments, flame retardants, and antibacterial agents. The amount of antioxidant used is 2 parts, and the antioxidant includes hindered phenolic primary antioxidants and phosphite auxiliary antioxidants mixed in a 1:2 weight ratio.
[0212] The UV stabilizer includes 0.5 parts of HALS light stabilizer.
[0213] The heat stabilizer includes 0.5 parts of tris(2,4-di-tert-butylphenyl) phosphite.
[0214] The lubricant comprises 0.5 parts pentaerythritol tetrastearate and 0.5 parts oxidized polyethylene wax.
[0215] 0.25 parts pigment, 0.25 parts flame retardant, and 0.5 parts antibacterial agent.
[0216] A method for preparing an environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition, involving an optimized manufacturing process for preparing the composition, comprising the environmentally friendly, high-content calcium carbonate bio-based thermoplastic elastomer composition as described above, including the following steps:
[0217] S1, dried bio-based thermoplastic resin and modified calcium carbonate;
[0218] S2. In a twin-screw extruder, the dried bio-based thermoplastic resin is melt-blended at a temperature of 120 to 230°C to form a continuous phase.
[0219] S3. Add natural rubber, vegetable oil-based plasticizer, interface compatibilizer, and additives to the continuous phase and apply shear force to mix them.
[0220] S4. Dry modified calcium carbonate is fed into the mixture from step S3 via a side feeder for fine dispersion.
[0221] S5. After the final mixture is extruded through the die and cooled, it is cut into granular shapes to obtain the finished product.
[0222] The bio-based thermoplastic resin is fed into the main feed port of the twin-screw extruder, the natural rubber, interface compatibilizer, and additives are fed into the first side feed port of the twin-screw extruder, the vegetable oil-based plasticizer is fed into the liquid injection port of the twin-screw extruder, and the modified calcium carbonate is fed into the second side feed port of the twin-screw extruder. The first side feed port is close to the main feed port, and the liquid injection port is located between the first side feed port and the second side feed port.
[0223] Comparative Example 1
[0224] Compared with Example 1, Comparative Example 1 differs in that its preparation process involves dry mixing 82 parts of SEBS resin with 6 parts of plasticizer paraffin oil, 10 parts of untreated ordinary calcium carbonate, and 2 parts of additives (including hindered phenolic primary antioxidants and phosphite auxiliary antioxidants mixed in a 1:2 weight ratio) in a drum mixer, and then compounding the mixture using the same twin-screw extruder at a temperature of 180-200°C to prepare granules. Comparative Example 1 uses SEBS block copolymer as the base resin with a styrene content of 30% and Kraton G1652 (Kraton Polymers).
[0225] Comparative Example 2
[0226] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses ordinary calcium carbonate instead of modified calcium carbonate, while the other components and preparation methods are the same as in Example 1.
[0227] Comparative Example 3
[0228] The difference between Comparative Example 3 and Example 2 is that Comparative Example 3 uses paraffin oil instead of vegetable oil-based plasticizer, while the other components and preparation methods are the same as in Example 2.
[0229] Comparative Example 4
[0230] The difference between Comparative Example 4 and Example 3 is that no interface compatibilizer is added in Comparative Example 4, while the other components and preparation methods are the same as in Example 3.
[0231] Comparative Example 5
[0232] The difference between Comparative Example 5 and Example 4 is that the bio-based thermoplastic resin used is a single polybutylene succinate, while the other components and preparation methods are the same as in Example 4.
[0233] Comparative Example 6
[0234] The difference between Comparative Example 6 and Example 5 is that the calcium carbonate used has a particle size of 8 μm, while the other components and preparation methods are the same as in Example 5.
[0235] Comparative Example 7
[0236] Compared with Example 1, Comparative Example 7 differs in that all materials are fed into the main feed port at once and mixed. The final mixture is extruded through the die head, cooled, and then cut into granular shapes to obtain the finished product. Other components are the same as in Example 1.
[0237] Comparative Example 8
[0238] Compared with Example 1, Comparative Example 8 differs in that natural rubber, vegetable oil-based plasticizer, interface compatibilizer, additives, and modified calcium carbonate are simultaneously added and mixed at the first feeding port, while no material is added at the second feeding port. The final mixture is extruded through a die and cooled before being cut into granular shapes to obtain the finished product. Other components are the same as in Example 1.
[0239] Comparative Example 9
[0240] Compared with Example 1, Comparative Example 9 differs in that no material is fed into the first feeding port, while natural rubber, vegetable oil-based plasticizer, interface compatibilizer, additives, and modified calcium carbonate are simultaneously fed into the second feeding port and mixed. The final mixture is extruded through a die and cooled, then cut into granular shapes to obtain the finished product. Other components are the same as in Example 1.
[0241] The composite materials of Examples 1 to 5 and Comparative Examples 1 to 9 were subjected to comprehensive testing.
[0242] The specific testing method is as follows:
[0243] The granules prepared for each example and comparative example were injection molded into samples for property testing using an injection molding machine (clamping force 120 tons).
[0244] The injection temperature was set at 150-170℃ for the example and 190-210℃ for the comparative example, while the mold temperature was maintained at 40℃.
[0245] The physical properties of the molded samples were determined as follows, and the results are shown in Tables 1 and 2.
[0246] (1) Tensile strength and elongation: Dumbbell-shaped No. 1 specimens were prepared according to ASTM D412 standard and measured using a universal testing machine at a tensile speed of 500 mm / min.
[0247] The strength at fracture and elongation are taken as tensile strength and elongation at fracture, respectively.
[0248] (2) Hardness: According to ASTM D2240 standard, five points on the flat surface of the sample were measured using a Shore A hardness tester, and the average value was calculated.
[0249] During the measurement, the value is read 3 seconds after the indenter contacts the sample.
[0250] (3) Resilience: The resilience was measured using a Lüpke resilience tester according to the internal test method (refer to ASTM D7121).
[0251] After a hammer is dropped from a specified height to impact the specimen, the rebound height is measured and expressed as a percentage (%). A higher value indicates better elastic recovery.
[0252] (4) Specific gravity: determined by water displacement method according to ASTM D792 standard.
[0253] (5) Microstructure observation: After the molded sample is frozen and fractured in liquid nitrogen, a platinum coating is applied to the fracture surface, and the microstructure is observed using a scanning electron microscope (SEM, FE-SEM, Hitachi S-4800) at magnifications of 5000x and 10000x.
[0254] Table 1. Performance test results of Examples 1 to 5
[0255] Test Project unit Test Standards Example 1 Example 2 Example 3 Example 4 Example 5 proportion - ASTM D792 1.45 1.32 1.48 1.50 1.35 Hardness (Shore A) - ASTM D2240 78 72 95 85 70 Tensile strength MPa ASTM D412 9.0 11.2 8.5 8.0 12.0 Elongation at break % ASTM D412 420 480 380 320 520 rebound rate % Internal methods 60 62 55 52 68
[0256] Table 2. Performance test results of Comparative Examples 1 to 9
[0257] Test Project unit Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 proportion - 0.95 1.46 1.30 1.51 1.48 1.42 1.45 1.45 1.45 Hardness (Shore A) - 75 82 68 98 92 80 75 76 74 Tensile strength MPa 10.5 4.2 7.5 5.8 9.0 5.2 6.2 5.5 4.8 Elongation at break % 550 120 280 150 270 210 240 220 180 rebound rate % 65 32 48 35 45 40 42 40 38
[0258] Table 3. Tensile stress-strain data for Example 1, Example 2 and Comparative Example 1.
[0259] strain(%) Example 1: Stress (MPa) Example 2: Stress (MPa) Comparative Example - Stress (MPa) 0 0 0 0 50 6 7 6.5 100 6.5 8 7.5 150 7 9 8 200 7.5 9.5 8.5 250 8 10 9 300 8.2 10.5 9.5 350 8.5 10.8 9.8 400 8.8 11 10 450 9 11.2 10.2 500 / 11.5 10.5 600 / / 11
[0260] As shown in Tables 1, 2, and 3 above, and Figure 1 The results confirmed that the compositions of Examples 1 and 2 of the present invention, despite containing a large amount of calcium carbonate, exhibited very good physical properties.
[0261] Figure 1This is a schematic diagram illustrating the internal microstructure of the environmentally friendly thermoplastic elastomer composition according to Example 1 of the present invention, observed using a scanning electron microscope (SEM). It shows an ideal phase structure in which natural rubber domains are finely dispersed within a continuous bio-based thermoplastic resin matrix, and surface-treated calcium carbonate particles are uniformly distributed without agglomeration. It indicates that the interfacial compatibilizer is located at the interface of each phase, forming a strong bond.
[0262] Table 3 shows stress-strain curves comparing the tensile properties of the compositions according to Examples 1 and 2 of the present invention with those of a conventional commercial petroleum-based TPR (SEBS-based) material as Comparative Example 1. It can be confirmed that, despite containing a high calcium carbonate content, the compositions of the present invention exhibit tensile behavior similar to or superior to that of the comparative example.
[0263] Specifically, in Example 1, 45 parts of calcium carbonate were added, resulting in a tensile strength of 9.0 MPa, an elongation of 420%, and a Shore A hardness of 78. This is a practical level comparable to the properties of existing commercial petroleum-based TPR (Comparative Example 1) with 10 parts of calcium carbonate (tensile strength 10.5 MPa, elongation of 550%, hardness 75). In particular, the resilience was also 60%, close to the 65% of Comparative Example 1, indicating excellent rubber elasticity. Example 2, with the calcium carbonate content reduced to 30 parts, showed further improvements in tensile strength (11.2 MPa) and elongation (480%) compared to Example 1, exhibiting superior strength and a similar level of flexibility. These results demonstrate that Examples 1 and 2 have the following advantages:
[0264] First, by properly blending bio-resin and natural rubber, a polymer matrix that balances flexibility and strength was obtained.
[0265] Second, the use of stearic acid-surface-treated calcium carbonate improves its affinity with the hydrophobic matrix, thereby inducing uniform dispersion that does not agglomerate even at high filler contents.
[0266] Third, through the synergistic effect of interface compatibilizers and vegetable oil-based plasticizers, the interfacial bonding force between bio-resin, natural rubber, and calcium carbonate is maximized, thereby improving resistance to external stress and delaying damage.
[0267] Although natural rubber is not a thermoplastic and does not completely melt into a liquid like resin, under the processing temperature (130-160°C) and the high shear force of the twin-screw extruder set in this invention, the rubber powder softens and becomes fluid, thereby being broken down and dispersed into micron-sized microdomains. For example... Figure 1 As shown, the bio-based thermoplastic resin (PBS / PCL / PLA) forms a continuous phase that encapsulates the dispersed phase of natural rubber domains. In other words, the natural rubber is encapsulated by the bio-resin.
[0268] Maleic anhydride-grafted polypropylene (MPP) effectively crosslinks the polymer matrix and inorganic fillers. Its polypropylene segments are physically entangled with natural rubber, while the grafted maleic anhydride groups form chemical bonds with the polar groups on the surface of the bioresin and calcium carbonate. Therefore, calcium carbonate particles are mainly distributed within the rubber domain and at the rubber-resin interface, with some dispersed in the resin matrix. The compatibilizer and plasticizer work together to ensure a tight bond between these three phases, preventing interfacial delamination under stress.
[0269] See Figure 1 The results of SEM observation of the microstructure confirmed that in the samples of Example 1 and Example 2, natural rubber domains of several micrometers in size were uniformly dispersed in the continuous phase of the bioresin, and fine calcium carbonate particles in monodisperse form without agglomeration were uniformly distributed around and inside them.
[0270] Furthermore, the fracture surface showed that the calcium carbonate particles fractured in a manner that was encapsulated by the matrix resin, rather than easily detaching from the matrix, indicating that the interfacial adhesion between the filler and the matrix was excellent.
[0271] Conversely, when using untreated ordinary calcium carbonate or calcium carbonate without interfacial compatibilizers (data not documented), calcium carbonate particles were observed to agglomerate into large aggregates and easily peel off at the interface, resulting in a significant decrease in physical properties.
[0272] In terms of specific gravity, Example 1 and Example 2 show a higher content of high-density calcium carbonate compared to the control group, but this is a favorable factor in reducing costs and will not be a major problem except for applications that require lightweighting.
[0273] In summary, this invention provides an innovative thermoplastic elastomer material technology that simultaneously achieves the advantages of environmental friendliness, price competitiveness, and excellent physical properties by combining bio-based materials and high-content, low-cost inorganic fillers in an optimal way and applying specialized interface control and process technologies.
[0274] The high filler content in Example 3 increases the material density and rigidity, but restricts molecular chain movement, resulting in a decrease in elongation and resilience compared to Example 1. The higher amount of natural rubber added allows it to maintain good elongation and resilience. The tensile strength of Example 3 is slightly higher than that of pure resin due to the high filler content, but lower than that of Example 1 with the optimized formulation.
[0275] The high filler content in Example 4 also resulted in high specific gravity and high hardness. The low amount of interfacial compatibilizer and low rubber content led to poor elasticity, resulting in lower resilience and elongation at break compared to other examples.
[0276] Compared to other examples, the high resin and rubber content of Example 5 makes the material softer and more elastic, with ample flexible segments providing high elongation, and moderate filler content and good interfacial bonding supporting high tensile strength.
[0277] The unmodified calcium carbonate used in Comparative Example 2 was prone to agglomeration, leading to severe stress concentration. Its tensile strength and elongation were significantly lower than those of Example 1. Its hardness was also higher than that of Example 1 due to agglomeration.
[0278] Comparative Example 3 uses paraffin oil instead of vegetable oil. Due to the poor compatibility between paraffin oil and bio-based polyester, it is easy to precipitate, resulting in insufficient plasticizing effect. Compared with Example 2, its hardness is lower and its strength is reduced.
[0279] Comparative Example 4, without the addition of an interface compatibilizer, exhibits extremely poor interfacial bonding between the resin, rubber, and filler phases, resulting in an unstable sea-island structure. Under stress, it is prone to interfacial peeling and whitening. Compared to Example 3, its strength and resilience are significantly reduced, while its hardness increases due to phase separation, and its resilience is poor.
[0280] Comparative Example 5 uses a single high-rigidity resin, whose properties cannot be complemented and optimized through blending, resulting in unbalanced performance and a higher hardness compared to Example 4.
[0281] Comparative Example 6 uses large-particle-size fillers. Large particles are prone to becoming stress concentration points, which leads to material embrittlement. As a result, its tensile strength and elongation are lower than those of Example 5, while its hardness is higher.
[0282] Comparative Example 7 involved a single-stage feeding process. The hydrophilic calcium carbonate readily undergoes severe secondary agglomeration before the hydrophobic resin melt forms. Furthermore, due to the different melting and softening characteristics of resin and rubber, a single-stage feeding results in the natural rubber not receiving sufficient shear force, remaining as large particles instead of forming fine island-like structures, ultimately leading to a sharp decline in the material's mechanical properties.
[0283] Comparative Example 8 involved adding filler and rubber in the same batch. The filler interfered with the dispersion and interfacial reaction of the rubber, resulting in severe agglomeration during the melting stage and poor dispersion. Its performance was slightly better than Comparative Example 7 but worse than Example 1.
[0284] Comparative Example 9 had insufficient mixing time with other components after resin plasticization, resulting in inadequate shear dispersion and uneven phase structure. Its various properties were the lowest among similar materials.
[0285] This invention provides an environmentally friendly thermoplastic elastomer composition that uses bio-based environmentally friendly resin and natural rubber as a polymer matrix, filled with a high content of inexpensive inorganic filler calcium carbonate, and possesses mechanical properties and injection molding processability equal to or better than existing petroleum-based TPE or TPR materials. This invention optimizes the type, content, and combination of the components constituting the composition, particularly by introducing a special additive system that maximizes the interfacial compatibility between the bio-resin, natural rubber, and inorganic filler, enabling the high content of inorganic filler to form a uniformly dispersed and stable phase structure within the polymer matrix.
[0286] The preparation method of the present invention is controllable, so as to prepare an environmentally friendly high-content calcium carbonate bio-based thermoplastic elastomer composition with high yield and excellent mechanical strength. The optimal manufacturing process conditions established by the present invention for preparing the composition can minimize the thermal decomposition of each component while inducing effective mixing and dispersion, and finally produce granules, thereby providing a manufacturing method that can be easily applied to various molding processes.
[0287] This invention provides a molded article prepared using an environmentally friendly thermoplastic elastomer composition. This molded article simultaneously meets excellent physical and environmental properties and can be used as a soft part in various industrial fields such as mobile device shells, wire sheaths, handles, and automotive interior materials.
[0288] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. An environmentally friendly, high-calcium carbonate bio-based thermoplastic elastomer composition, characterized in that: By weight, the composition includes 10-45 parts of bio-based thermoplastic resin, 5-15 parts of natural rubber, 30-55 parts of modified calcium carbonate, 3-10 parts of vegetable oil-based plasticizer, 0.5-5 parts of interface compatibilizer, and 0-5 parts of additives. The bio-based thermoplastic resin forms a continuous phase matrix, and the natural rubber forms a dispersed phase within the bio-based thermoplastic resin matrix. The bio-based thermoplastic resin includes a combination of polybutylene succinate, polycaprolactone, and polylactic acid; or a combination of polybutylene succinate, polylactic acid, polybutylene terephthalate-adipate, and polyhydroxyalkanoates; or a combination of polybutylene succinate, polycaprolactone, polylactic acid, polybutylene terephthalate-adipate, and polyhydroxyalkanoates. Interface compatibilizers include one or more combinations of maleic anhydride-grafted polyolefins, copolymers containing glycidyl methacrylate, diphenylmethane diisocyanate, and vinyltriethoxysilane. The modified calcium carbonate is calcium carbonate that has undergone dry surface modification with a surface treatment agent. The surface treatment agent includes one or more combinations of stearic acid, titanate coupling agent, aluminate coupling agent, stearate, oleate, and palmitate. The average particle size of the modified calcium carbonate is 0.5 to 5 µm, and the amount of surface treatment agent is 0.5 to 3.0% of the total weight of calcium carbonate. The modified calcium carbonate is distributed in a monodisperse form in the continuous phase and the dispersed phase. The environmentally friendly, high-calcium carbonate bio-based thermoplastic elastomer composition is prepared by a method comprising the following steps: S1, dried bio-based thermoplastic resin and modified calcium carbonate; S2. In a twin-screw extruder, the dried bio-based thermoplastic resin is melt-blended at a temperature of 120 to 230°C to form a continuous phase. S3. Add natural rubber, vegetable oil-based plasticizer, interface compatibilizer, and additives to the continuous phase and apply shear force to mix them. S4. Dry modified calcium carbonate is fed into the mixture from step S3 via a side feeder for fine dispersion. S5. After the final mixture is extruded through a die and cooled, it is cut into granular shapes to obtain the finished product; The bio-based thermoplastic resin is fed into the main feed port of the twin-screw extruder. The natural rubber, interface compatibilizer, and some additives are fed into the first side feed port of the twin-screw extruder. The vegetable oil-based plasticizer is fed into the liquid injection port of the twin-screw extruder. The modified calcium carbonate is fed into the second side feed port of the twin-screw extruder. The first side feed port is close to the main feed port, and the liquid injection port is located between the first side feed port and the second side feed port.
2. The environmentally friendly high-content calcium carbonate bio-based thermoplastic elastomer composition according to claim 1, characterized in that: Vegetable oil-based plasticizers include one or more combinations of epoxidized soybean oil and epoxidized linseed oil, and the composition also includes citrate plasticizers.
3. The environmentally friendly high-content calcium carbonate bio-based thermoplastic elastomer composition according to claim 1, characterized in that: The additives include one or more of antioxidants, ultraviolet stabilizers, heat stabilizers, lubricants, pigments, flame retardants, and antibacterial agents. The amount of antioxidants used is 0.1 to 3 parts. The antioxidants include hindered phenolic primary antioxidants and phosphite auxiliary antioxidants mixed in a weight ratio of 1:1 to 1:
3.
4. The application of the environmentally friendly high-content calcium carbonate bio-based thermoplastic elastomer composition according to any one of claims 1-3, characterized in that, This environmentally friendly, high-calcium carbonate bio-based thermoplastic elastomer composition is prepared into finished products through one or more of the following processes: injection molding, extrusion molding, blow molding, and 3D printing. The finished products include mobile device housings, wire and cable sheathing materials, tools, handles, shoe soles, toys, and automotive interior parts.
Citation Information
Patent Citations
Biodegradable polymeric material, biodegradable product and manufacturing method and application thereof
CN117480215A
High-strength high-deformation bio-based polyester elastomer and preparation method thereof
CN120059430A